Immobilization of Superoxide Dismutase in Mesoporous Silica and its Applications in Strengthening the Lifespan and Healthspan of Caenorhabditis elegans - Yang, Yiling; Wang, Wenbin; Liu, Kefeng; Zhao, Jie (Frontiers in Bioengineering and Biotechnology, 2022)
Senescence is a major inductive factor of aging-related diseases in connection with an accumulation of reactive oxygen species (ROS). Therefore, it’s important to maintain ROS at an appropriate level to keep homeostasis in organisms. Superoxide dismutase (SOD) is a vital enzyme in defensing against oxidative damage in vivo. Because of the defects in the direct application of SOD and SOD mimics, mounting delivery systems have been developed for the efficient applications of SOD to realize antioxidant treatment. Among these systems, mesoporous silica nanoparticles (MSN) has been widely studied because of various advantages such as desirable stability, low toxicity and adjustable particle sizes. Herein, SOD was immobilized on MSN through physical absorption strategy to construct nanosystem SOD@MSN and The nematode Caenorhabditis elegans (C. elegans) was selected as the model organism for the subsequent antioxidant and anti-aging studies. The research results suggested the nanosystem could not only be effectively internalized by C. elegans but also protect nematode against external stress, thus extending the lifespan and healthspan of C. elegans. Therefore, SOD@MSN could be applied as a promise medicine in anti-aging therapeutics.